SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF RUTHENIUM NITROSYL COMPLEXES CONTAINING POLYPYRIDYL LIGANDS - Dayana P. S. Penha; Thuanny M. de Sousa; Dayane C. de Oliveira; Maria R. H. da Silva; Verônica da S. Oliveira; Daniel de L. Pontes; Ana C. F. de B. Pontes; Tércio de F. Paulo; Francisco O. N. da Silva (Química Nova)
The ruthenium(II) complexes cis-[Ru(bpy)(phen)(ImN)(NO)](PF6)3 (I) and cis-[Ru(bpy)(phen)(SO3)(NO)](PF6) (II) (bpy = 2,2’-bipyridine, phen = 1,10’-phenanthroline and ImN = imidazole) were synthesized and characterized using UV-visible, infrared and NMR (nuclear magnetic resonance) spectroscopies and electrochemical techniques. Infrared bands in the 1910-1950 cm−1 range are consistent with NO+ stretching, indicating the coordination of nitric oxide. The UV-Vis results allowed for the identification of intraligand bands of bipyridine and phenanthroline ligands, as well as metal-to-ligand charge transfer (MLCT) bands for both polypyridine ligands in the wavelength range of 320 to 400 nm. Additionally, an MLCT band for the nitrosyl ligand was observed at about 469 nm. The voltammogram profiles displayed a single quasi-reversible process at 219 mV (complex I) and -102 mV (complex II), with both processes being related to the NO+/0 redox pair. The photochemical behavior of these complexes was studied, and NO release was observed upon blue light irradiation. The antibacterial activity of the complexes was tested against the bacteria Staphylococus aureus, Staphylococcus epidermidis and Pseudomonas aeruginosa, based on minimum inhibitory concentration measurements, in which no or moderate activity was observed against Gram-positive bacteria. However, complexes I and II showed good antimicrobial activity against Gram-negative Pseudomonas aeruginosa strains, being able to inhibit growth at low concentrations of 57.23 µmol L−1 for complex I and 200.8 µmol L−1 for complex II.